2018
DOI: 10.1063/1.5028454
|View full text |Cite
|
Sign up to set email alerts
|

Gauge-origin dependence in electronic g-tensor calculations

Abstract: We present a benchmark study on the gauge-origin dependence of the electronic g-tensor using data from unrestricted density functional theory calculations with the spin-orbit mean field ansatz. Our data suggest in accordance with previous studies that g-tensor calculations employing a common gauge-origin are sufficiently accurate for small molecules; however, for extended molecules, the introduced errors can become relevant and significantly exceed the basis set error. Using calculations with the spin-orbit me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 74 publications
0
18
1
Order By: Relevance
“…The gauge dependence of the g tensor is less pronounced than that for the NMR orbital contribution. However, it still leads to comparably large deviations for systems with a spatially extended spin-density distribution. , Therefore, the spin–orbit perturbation term with GIAOs and the X2C picture-change correction needs to be used and becomes As shown for the PSOSO term, the extension for the mSNSO/SNSO approximation is trivial and we list the equations without this approximation in this subsection for brevity.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The gauge dependence of the g tensor is less pronounced than that for the NMR orbital contribution. However, it still leads to comparably large deviations for systems with a spatially extended spin-density distribution. , Therefore, the spin–orbit perturbation term with GIAOs and the X2C picture-change correction needs to be used and becomes As shown for the PSOSO term, the extension for the mSNSO/SNSO approximation is trivial and we list the equations without this approximation in this subsection for brevity.…”
Section: Theorymentioning
confidence: 99%
“…However, it still leads to comparably large deviations for systems with a spatially extended spin-density distribution. 52,140 Therefore, the spin− orbit perturbation term with GIAOs and the X2C picturechange correction needs to be used and becomes…”
Section: The Journal Of Physical Chemistrymentioning
confidence: 99%
“…For a single local paramagnetic center, it has been demonstrated that choosing a gauge origin close to the paramagnetic center usually yields good results. 47 The gauge-origin dependence can be removed by employing gaugeincluding AOs (GIAOs). 48,49 However, this makes the theory significantly more complicated at not much added conceptual insight.…”
Section: Please Cite This Article As Doi:101063/50088162mentioning
confidence: 99%
“…However, the RKB condition is generally sufficient to recover the nonrelativistic limit for first-order derivatives. The g tensor is commonly obtained with spin–orbit perturbation theory in one-component approaches. ,, Here, inclusion of the vector potential in the Pauli spin–orbit operator leads to the relativistic mass or Pauli kinetic energy correction and the diamagnetic or gauge correction. , Therefore, using RMB ensures that the two-component approach is directly comparable to the perturbative ansatz. Whereas the use of RMB leads to problematic integrals for the HFC constant and the related nuclear magnetic resonance (NMR) coupling constants in X2C, the integrals can be evaluated straightforwardly for magnetic field derivatives. , Thus, RMB can be used for EPR g tensors similar to NMR shieldings , and magnetic circular dichroism …”
Section: Introductionmentioning
confidence: 99%